Poor sleep quality in systemic lupus erythematosus: does it depend on depressive symptoms?. (November 2014) - Palagini, L; Tani, C; Bruno, R M; Gemignani, A; Mauri, M; Bombardieri, S; Riemann, D; Mosca, M
Objectives: Sleep disturbances are frequently observed in rheumatic diseases including systemic lupus erythematosus (SLE). This study aimed at evaluating the prevalence of insomnia, poor sleep quality and their determinants in a cohort of SLE patients. Methods: Eighty-one consecutive SLE female patients were evaluated in a cross-sectional study. The Pittsburgh Sleep Quality Index (PSQI), the Insomnia Severity Index (ISI), the Beck Depression Inventory (BDI) and the Self-rating Anxiety Scale (SAS) were administered. Patients with previous diagnosis of obstructive sleep apnea or restless legs syndrome were excluded. Fifty-three women with hypertension (without SLE) were enrolled as control group (H). Results: In the SLE cohort poor sleep quality (65.4% vs 39.6%, p  < 0.01) and difficulty in maintaining sleep and/or early morning awakening (65.4% vs 22.6%, p  < 0.001), but not insomnia (33.3% vs 22.6%, p  = ns), were more prevalent than in H. Depressive symptoms were present in 34.6% of SLE vs 13.2% H patients ( p  < 0.001) while state anxiety was more common in H patients (H 35.8% vs SLE 17.3%, p  < 0.005). SLE was associated with a 2.5-times higher probability of presenting poor sleep quality in comparison to H (OR 2.5 [CI 1.21–5.16]). After adjusting for confounders, both depressive symptoms (OR 4.4, [1.4–14.3]) and use of immunosuppressive drugs (OR 4.3 [CI 1.3–14.8]) were significantly associated with poor sleep quality in SLE patients. Furthermore, poor sleep quality was not associated either with disease duration or activity. Conclusions: In a cohort of SLE women, insomnia and poor sleep quality, especially difficulties in maintaining sleep, were common. Depressive symptoms might be responsible for the higher prevalence of poor sleep quality in SLE.